Resminostat plus sorafenib as second-line therapy of advanced hepatocellular carcinoma: the SHELTER study - Bitzer, Michael; Ganten, Tom M. (Journal of hepatology, 2016)
Background & Aims No established therapies for patients with hepatocellular carcinoma (HCC) and progression on first-line sorafenib treatment currently exist. This phase I/II trial investigated safety, pharmacokinetics and potential biomarkers of the histone deacetylase inhibitor resminostat and a combination therapy with resminostat and sorafenib. Methods Patients with HCC and radiologically confirmed progression on sorafenib were treated in an exploratory, multi-center, open-label, uncontrolled, non-randomized, parallel group phase I/II study. In the combination group (n=38) four dose levels ranged from daily 200 to 600mg resminostat plus 400 to 800mg sorafenib. The monotherapy group (n=19) received 600mg resminostat. Results 57 patients received treatment. Most common adverse events were gastrointestinal disorders, thrombocytopenia and fatigue. Median maximal histone deacetylase inhibition and highest increase in H4-acetylation matched Tmax of resminostat. Sorafenib or the Child-Pugh score did not affect typical pharmacokinetics characteristics of resminostat. Efficacy assessment as progression-free survival-rate after 6 treatment cycles (12weeks, primary endpoint) was 12.5% for resminostat and 62.5% for resminostat plus sorafenib. Median time to progression and overall survival were 1.8 and 4.1months for resminostat and 6.5 and 8.0months for the combination, respectively. Zinc finger protein 64 (ZFP64) baseline expression in blood cells was found to correlate with overall survival. Conclusions The combination of sorafenib and resminostat in HCC patients was safe and showed early signs of efficacy. Sorafenib did not alter the pharmacokinetic profile of resminostat or its histone deacetylase inhibitory activity in vivo. A prognostic and potentially predictive role of ZFP64 for treatment with resminostat should be further investigated in HCC and possibly other cancer indications. Lay summary No established therapy for patients with advanced hepatocellular carcinoma and progression under first-line systemic treatment with sorafenib currently exists. Epigenetic modulation by inhibition of histone deacetylases might be able to overcome therapy resistance. This exploratory phase I/II clinical study in patients with radiologically confirmed progression under first-line treatment with sorafenib investigated the histone deacetylases inhibitor resminostat as single agent or in combination with continued application of sorafenib. Clinical trial registration The clinical trial has been registered at www.clinicaltrials.gov as NCT00943449.
Gesehen am 21.11.2018